Ezra, Nehemiah introduction, translation and notes - Myers, Jacob M. (Garden City, N.Y. Doubleday, 1965)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Nehemiah -- commentaries